Characterization of microstructure and tensile fracture behavior in a novel infiltrated TiC–steel composite. (February 2016) - Oh, N.R.; Lee, S.K.; Hwang, K.C.; Hong, H.U.
Abstract: The tool steel matrix composite was successfully produced by a novel infiltration method so as to have TiC reinforcement particles more than 57 vol.%. The interface between α-Fe and TiC was found to be semi-coherent nature and the orientation relationship was clearly confirmed, i.e. [012]α-Fe  // [110]TiC, (200)α-Fe  //  2 ¯ 24 TiC . Tensile fractures consisted mainly of {100} microcleavage of TiC grains with no interfacial decohesion. The increased strength of the composite at 700 °C is rationalized in terms of mutually interactive influences of load transfer mechanism and the matrix strengthening resulted from the increased density of dislocations. Graphical abstract: